Early man; prehistory and the civilizations of the ancient Near East - Starr, Chester G., 1914-1952. (New York, Oxford University Press, 1973)
Traces the development of man from the earliest food-gatherers through the origins of civilization to the consolidation of the Persian Empire.
Bibliography: p. 195-199.
Keywords: Prehistoric peoples; Civilization, Ancient; Middle East -- Civilization -- To 622.; Middle East -- Civilization